Reduction and geometric samplings - Mikityuk , I. V.; Prikarpatsky , A. K. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A construction is created that makes it possible to geometrically quantize a reduced Hamiltonian system using the procedure of geometric quantization realized for a Hamiltonian system with symmetries (i.e., to find the discrete spectrum and the corresponding eigenfunctions, if these have been found for the initial system). The construction is used to geometrically quantize a system obtained by reduction of a Hamiltonian system that determines the geodesic flow on an n-dimensional sphere.